A REVIEW ON IPOMOEA CARNEA - A. SHARMA; R. K. BACHHETI (International Journal of Pharma and Bio Sciences, 2013)
The plant Ipomoea Carnea belongs to family Convolvulaceae, It was used in ancient system of medicine in many countries but not to great extent. The fact is that the plant had immense potential as an Anti-Inflammatory Activity, Antioxidant Activity, Antidiabetic Activity, Antimicrobial Activity, Wound Healing Activity, Immunomodulatory Activity, Cardiovascular Activity, Embryotoxic effect, Antifungal Activity, Hepatoprotective Activity, Inhibition Activity and Anxiolytic Properties. The present aim of study is to review the potential of Ipomoea Carnea with reference to its Phytochemical, pharmacological and other activities.